Characterisation of Palmera dairy goat production systems - Escuder A.; Fernández G.; Capote J. (Analyse technico-économique des systèmes de production ovine et caprine : méthodologie et valorisation pour le développement et la prospective., 2006)
The objective of this paper was the analysis of Palmera goat breed farms in the Isle of La Palma in the Canary Islands and to evaluate the suitability of the survey under these conditions. The study included 46 production variables, and it was performed on 21 farms. Production data were taken from the farmers' records and also by direct observation; however, some of the parameters may have been estimated. It was necessary to adapt the survey to local conditions and use trained people to collect the data. The statistical analysis showed a high degree of homogeneity between the farms, with many aspects in common, and low variation coefficients. Negative correlation was found between the size of herd and the net margin per litre of milk (-0.26) and positive between the same margin and natural grassland area per goat (0.28) and the age of the farm (0.35), the number of years the farm has been functioning. ANOVA analysis showed that the management System only influenced (p< 0.05) milk production per goat (509.81 ± 94.3 I in intensive vs. 422.87 ± 71.8 I in other systems) and the survival of kids per goat (1.69 ± 0.36 kids vs. 1.19 ± 0.40 kids) and, consequently income from kid meat / goat (35.37 ± 9.57 € vs. 23.95 ± 6.9 €).
Séminaire du sous-réseau Systèmes de Production du réseau Interrégional FAO-CIHEAM de recherche et développement sur les ovins et caprins, 2005/06/16-18, Seville (Spain)